Evidence of improving survival of patients with rectal cancer in France: a population based study. Issue 3 (1st March 1999) - Finn-Faivre, C; Maurel, J; Benhamiche, A M; Herbert, C; Mitry, E; Launoy, G; Faivre, J
Abstract : BACKGROUND: Over the past 20 years there have been many changes in the management of rectal cancer. Their impact on the overall population is not well known. AIMS: To determine trends in management and prognosis of rectal cancer in two French regions. SUBJECTS: 1978 patients with a rectal carcinoma diagnosed between 1978 and 1993. METHODS: Time trends in treatment, stage at diagnosis, operative mortality, and survival were studied on a four year basis. A non-conditional logistic regression was performed to obtain an odds ratio for each period adjusted for the other variables. To estimate the independent effect of the period a multivariate relative survival analysis was performed. RESULTS: Over the 16 year period resection rates increased from 66.0% to 80.1%; the increase was particularly noticeable for sphincter saving procedures (+30.6% per four years, p=0.03). The percentage of patients receiving adjuvant radiotherapy increased from 24.0% to 40.0% (p=0.02). The proportion of patients with Dukes' type A cancer increased from 17.7% to 30.6% with a corresponding decrease in those with more advanced disease. Operative mortality decreased by 31.1% per four years (p=0.03). All these improvements have resulted in a dramatic increase in relative survival (from 35.4% for the 1978–1981 period to 57.0% for the 1985–1989 period). CONCLUSIONS: Substantial advances in the management of rectal cancer have been achieved, but there is evidence that further improvements can be made in order to increase survival.